Effective Classroom Management to Create a Positive Learning Environment - Tri Hasnanto, Anton (CV. Tripe Konsultan, 2024)
Effective classroom management is essential for creating a positive learning environment that fosters student engagement and academic success. Learning is a conscious and planned effort to create a learning atmosphere and educational process so that students actively improve their abilities, so that the educational process should be able to produce a classroom atmosphere that is conducive to supporting the creation of a quality educational process. The purpose of this research is to describe the implementation of classroom management, creating a positive environment for learning, being a good communicator, dealing with student problem behavior. The methodology used to create this article is to use literature review procedures. Researchers use this method because researchers want to understand and master classroom management in producing positive educational areas using a literature research approach. Based on the results of the literature study, it can be concluded that education is a planned effort to realize the learning process so that students can actively develop their potential, and teachers have an obligation to realize educational ideals and goals. Students need a positive environment for learning, so there needs to be a class management strategy, so that goals can be achieved easily, so the learning process should be able to create a classroom atmosphere or classroom climate that is conducive to supporting the creation of quality learning processes. It is hoped that in the next research the researchers will be able to find new things that can increase students' enthusiasm for learning.